1990
DOI: 10.1093/oxfordjournals.eurheartj.a059743
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the mitochondrial respiratory chain in human dilated cardiomyopathy

Abstract: The defects underlying the impairment of systolic pump function in human dilated cardiomyopathy (DCM) are not known. We isolated mitochondrial particles from 10 hearts of transplant recipients with DCM and from nine normal hearts not used for transplantation. Yield was similar in both groups (2.77 vs 2.81 mg mitochondrial protein per gram heart). Cytochrome content (difference spectrophotometry) was found reduced in DCM mitochondria, e.g. cytochrome c was 0.295 +/- 0.06 in the DCM group and 0.371 +/- 0.04 mumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 0 publications
4
52
0
Order By: Relevance
“…Mitochondrial function changes during development and is altered in failing human hearts (10,32). We found a decrease in three of seven mitochondrial multicomplex units in THFdTGR with our chip approach (cytochrome B, cytochrome c oxidase, ATP synthase).…”
Section: Cardiac Gene Expression In Dtgrmentioning
confidence: 67%
“…Mitochondrial function changes during development and is altered in failing human hearts (10,32). We found a decrease in three of seven mitochondrial multicomplex units in THFdTGR with our chip approach (cytochrome B, cytochrome c oxidase, ATP synthase).…”
Section: Cardiac Gene Expression In Dtgrmentioning
confidence: 67%
“…End-stage HF was associated with multiple mitochondrial functional injuries, e.g., a decrease of ETC activities per muscle mass, most notably CI (Scheubel et al 2002), CIII (Buchwald et al 1990;Jarreta et al 2000;Marin-Garcia et al 1995), and CIV (Arbustini et al 1998;Quigley et al 2000), and a decrease in OXPHOS capacity in the presence of substrates directing electrons into CI in permeabilized fibers (Saks et al 1991;Sharov et al 2000). Part of the loss of mitochondrial ETC activity or OXPHOS per g of muscle is explainable by a decrease in mitochondrial content occurring also in endstage HF (Kalsi et al 1999;Nascimben et al 1996;Quigley et al 2000).…”
Section: Anatomical Sites In the Heartmentioning
confidence: 99%
“…Furthermore, several studies have shown that mitochondrial disorders often present themselves as cardiomyopathies. For example, mutations that decrease mitochondrial oxidative phosphorylation or alter the activity of proteins involved in the transport of mitochondrial substrates (such as adenine nucleotide and fatty acid transporter proteins), can cause cardiac hypertrophy, as can the depletion of mitochondrial DNA itself (Buchwald et al, 1990;Graham et al, 1997;Stojanovski et al, 2004).…”
Section: Introductionmentioning
confidence: 99%